Ovarian inguinal hernia - a possibility in MURCS syndrome - Rahul Saini; Lovenish Bains; Tarangpreet Kaur; Pawan Lal; Veer Pal; Mohd Yasir Beg; Daljit Kaur (BMC, 2021)
Abstract Background Inguinal hernia containing ovary and fallopian tube can be found in paediatric population and is a rare finding in women of reproductive age group. Most of the cases are associated with congenital abnormalities of the female genital tract. Case presentation A 20 year old female presented with right reducible inguinal hernia, primary amenorrhea and normal secondary sexual characteristics. Clinical examination revealed scoliosis with convexity towards left side, prominence of left rib cage with Sprengel deformity and right sided heart sounds. Ultrasound of the inguinal swelling revealed right ovary within the hernial sac, Chest X-ray revealed right lung collapse and dextrocardia. Further Magnetic resonance imaging (MRI) of pelvis revealed inguinal hernia with right ovary as its content, normal left ovary and absent uterus. Computed tomography (CT) revealed complete collapse of right lung with compensatory left lung hyperinflation and absent right kidney. Karyotyping of the patient was normal, 46XX. A diagnosis of MURCS syndrome with right ovarian hernia was made. The hernia was surgically managed with repositioning of ovary and fallopian tube into the pelvis. Discussion Ovary in inguinal hernia is rare in women of reproductive age group. MRKH syndrome, a mullerian duct anomaly, is the congenital aplasia of uterus and upper two-thirds of vagina in a female with normal ovaries, fallopian tube, secondary sexual characteristics and 46XX karyotype. MURCS is a subtype of MRKH type 2 having mullerian duct agenesis with renal, cardiac, muscular & vertebral defects. General physical examination and primary investigations if yields abnormal findings; the patient must undergo an array of investigations to rule out MRKH/MURCS, or other congenital abnormality. Early diagnosis is essential to prevent its incarceration or torsion. The primary treatment of ovary in inguinal hernia is repositioning the ovary and fallopian tube back to pelvis to preserve fertility and repair of inguinal hernia. A multidisciplinary team is required to deal with various abnormalities present in a patient with MURCS.